Katalog der in den Sammlungen des Deutschen Entomologischen Institutes aufbewahrten Typen - II (Dermaptera, Mantodea, Blattariae, Isoptera, Phasmida, Saltatoria). - Petersen, Günther; Gaedike, Hannelore (Contributions to Entomology = Beiträge zur Entomologie, 1970)
There is presented the second part of a catalogue of type specimens preserved in the collections of the Deutsches Entomologisches Institut.Nomenclatural Actsstriata Willemse, 1932 (Gelastorrhinus), Lectotype